1997
DOI: 10.1007/s001340050329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of norepinephrine and dobutamine to epinephrine for hemodynamics, lactate metabolism, and gastric tonometric variables in septic shock: a prospective, randomized study

Abstract: Considering the global hemodynamic effects, epinephrine is as effective as norepinephrine-dobutamine. Nevertheless, gastric mucosal acidosis and global metabolic changes observed in epinephrine-treated patients are consistent with a markedly inadequate, although transient, splanchnic oxygen utilization. The metabolic and splanchnic effects of the combination of norepinephrine and dobutamine in hyperdynamic dopamine-resistant septic shock appeared to be more predictable and more appropriate to the current goals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
1
26

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(220 citation statements)
references
References 36 publications
8
185
1
26
Order By: Relevance
“…The role of epinephrine in patients with septic shock is unclear. Although studies such as those by Seguin et al 51 and Levy et al 52 have shown a difference in hemodynamic parameters and measures of tissue perfusion, two RCTs comparing norepinephrine (+ dobutamine where indicated) to epinephrine did not show a difference in mortality. 20,53 The 2012 Surviving Sepsis Guidelines recommend the addition of epinephrine to norepinephrine "when [an] additional agent is needed to maintain adequate blood pressure".…”
Section: Question 5: Which Vasopressors and Inotropes Should Be Used mentioning
confidence: 88%
“…The role of epinephrine in patients with septic shock is unclear. Although studies such as those by Seguin et al 51 and Levy et al 52 have shown a difference in hemodynamic parameters and measures of tissue perfusion, two RCTs comparing norepinephrine (+ dobutamine where indicated) to epinephrine did not show a difference in mortality. 20,53 The 2012 Surviving Sepsis Guidelines recommend the addition of epinephrine to norepinephrine "when [an] additional agent is needed to maintain adequate blood pressure".…”
Section: Question 5: Which Vasopressors and Inotropes Should Be Used mentioning
confidence: 88%
“…Rationale The physiologic effects of vasopressors and combined inotrope/vasopressor selection in septic shock are outlined in an extensive number of literature reviews [252][253][254][255][256][257][258][259][260][261]. Norepinephrine increases MAP due to its vasoconstrictive effects, with little change in heart rate and less increase in stroke volume compared with dopamine.…”
Section: G Vasoactive Medicationsmentioning
confidence: 99%
“…It is less commonly used as the first line therapy for septic shock. But there are still many investigations on the effectiveness of epinephrine (14,15,(22)(23)(24)(25)(26). Subjects in these trials were randomized to receive either epinephrine alone or norepinephrine plus dobutamine, because norepinephrine has only moderate effect on the cardiac β1 receptor.…”
Section: Dopamine and Norepinephrinementioning
confidence: 99%
“…Clinical studies yielded conflicting results with respect to the effect of dobutamine on left ventricular stroke work index, mean arterial pressure and mean pulmonary artery pressure (29)(30)(31)(32)(33) (14). Other studies also failed to draw a definitive conclusion (15,(23)(24)(25).…”
Section: Dobutaminementioning
confidence: 99%